Предмет:
МатематикаАвтор:
анонимРаскроем скобки и упростим выражения:
1) m * (m^2 - m) + (m^2 - m + 1) = m^3 - m^2 + m^2 - m + 1 = m^3 - m + 1;
-m^2 + m^2 = 0;
2) 5n^2 * (3n + 1) - 2n * (5n^2 - 3) = 15n^3 + 5n^2 - 10n^3 + 6n = 5n^3 + 5n^2 + 6n;
15n^3 - 10n^3 = 5n^3;
3) p * (p^2 - 2a) + a * (2p - a^2) = p^3 - 2ap + 2ap - a^3 = p^3 - a^3;
-2ap + 2ap = 0;
4) x * (x^3 + x^2 + x) - (x^3 + x^2 + x) = x^4 + x^3 + x^2 - x^3 - x^2 - x = x^4 - x;
x^3 - x^3 = 0;
x^2 - x^2 = 0.
Автор:
breannaoohdДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть